Role of adjuvant therapy in the treatment of helicobacter pylori infection in children. - O. N. Gerasymenko (Medičnì Perspektivi, 2014)
The aim was to study the effect of combined probiotic containing Lactobacillus acidophilus, Bifidobacterium infantis, Enterococcus faecium, on H.pylori eradication efficacy in the treatment of children with chronic H.pylori- associated gastroduodenitis in the scheme of "triple" therapy of H.pylori eradication. Determination of total serum Ig M , A, G protein to Ag SagA H. pylori, breathing "Helik" test, rapid urease "Helpil" test ; that of concentration of serum sCD14 was conducted. The study group included 20 children who received standard "triple" eradication therapy for 7 days and 1 caps. of probiotic 3 times a day for 4 weeks, control group (20 children) – who received only standard eradication therapy. It is shown that combined use of probiotics in the treatment of Helicobacter pylori infection enhances effectiveness of eradication of H.pylori. In the basis of action of probiotic strains of the drug is an anti-inflammatory effect mediated by the impact on non-specific mechanisms of innate immunity, provided by molecular mechanism responsible for induction of sCD14 synthesis.